2013
DOI: 10.1080/09639284.2013.766015
|View full text |Cite
|
Sign up to set email alerts
|

Developing Accounting Students' Listening Skills: Barriers, Opportunities and an Integrated Stakeholder Approach

Abstract: Accountants and employers of accounting graduates consider listening to be among the most important communication skills that graduates possess. However, accounting education practices that develop students' listening skills are uncommon. Further, in the case of listening development, the current approach of prescribing that educators do more to rectify students' skill deficiencies overlooks barriers that prevent greater incorporation of listening instruction in the accounting curriculum. An alternative integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 78 publications
0
20
0
3
Order By: Relevance
“…However, further investigation indicated that the authors were, indeed, acquainted with the research on listening skills. For example, one of the authors of O'Connell et al (2015) was the head of school in which Stone et al (2013) produced their high-impact article on 'The nature and significance of listening skills in accounting practice'; also, the earlier article, Stone and Lightbody (2012). These articles were not cited.…”
Section: Post 2009 Pronouncementsmentioning
confidence: 99%
“…However, further investigation indicated that the authors were, indeed, acquainted with the research on listening skills. For example, one of the authors of O'Connell et al (2015) was the head of school in which Stone et al (2013) produced their high-impact article on 'The nature and significance of listening skills in accounting practice'; also, the earlier article, Stone and Lightbody (2012). These articles were not cited.…”
Section: Post 2009 Pronouncementsmentioning
confidence: 99%
“…Listening is regarded as a soft skill employability factor and even as an "indispensable attribute" to effective practice in a profession (Stone, Lightbody, & Whait, 2013). Listening is pivotal to learning as well as enhancing students' future employment opportunities.…”
Section: Materials Theoretical Backgroundmentioning
confidence: 99%
“…Journal of Language andEducation, 3(3), 60-67. doi:10.17323/2411-7390-2017-3-3-60-67 FOSTERING ECONOMICS STUDENTS' LISTENING SKILLS THROUGH SELF-REGULATED LEARNING of the amount of the classroom-based EFL learning within higher education in Russia overall. As a result, classroom-based study mode provides little space for the development of listening skills (Stone, Lightbody & Whait, 2013). Limited time available for fostering students' listening skills and face-to-face interaction (Parker, 2011) is partly the result of the global tendency to run larger classes and introduce a greater number of professional subjects in higher education.…”
mentioning
confidence: 99%
“…Much of this research is on professional competency developments (Bloch, Brewer, & Stout, 2012;Craig & McKinney, 2010;Fortin & Legault, 2010;Stone, Lightbody, & Whait, 2013;Young & Warren, 2011) with little emphasis on initiatives directed towards professional examinations (Flood & Wilson, 2008). One of the reasons could be that although accounting professions generally influence accounting academia (Evans & Juchau, 2009), such influence is reflected in the curriculum and the teaching and assessment of programmes being offered (Venter & De Villiers, 2013).…”
Section: Features Of Support Programmes In Particular the Thuthuka Pmentioning
confidence: 99%